Penerapan Prinsip Hukum dan Etika dalam Praktik Bisnis: Pelatihan untuk Meningkatkan Kesadaran Hukum di Kalangan Pengusaha Muda Kota Jayapura - Muhammad Khaidir Kahfi Natsir; Dwight Nusawakan; Abdul Malik Mufty; Annisa Fitriah Mudassir; Ika Fitrianita; Magdhalena Tasik Todingrara; Ayub Jose Luhut Parulian Simanjuntak (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
In the context of rapid economic development, young entrepreneurs in Jayapura City face the challenge of understanding and applying the principles of law and ethics in their business practices. Law and ethics are essential foundations for creating a sustainable and responsible business environment. This research aims to evaluate the effectiveness of a training program designed to enhance legal awareness among young entrepreneurs. The training includes the delivery of material on business law, consumer protection, and business ethics, as well as interactive discussions and case studies. The methods used in this study include data collection through pre-training and post-training questionnaires, as well as in-depth interviews with participants. The analysis results show a significant increase in participants' understanding of legal and ethical business principles, with average questionnaire scores rising from 55% to 85% after the training. These findings indicate that the training not only enhances participants' knowledge but also builds their confidence in applying legal and ethical principles in their daily business practices. Therefore, this training program is expected to contribute to the development of better and more responsible business practices in Jayapura City.